SARS-CoV-2 titers in wastewater are higher than expected from clinically confirmed cases - Fuqing Wu; Amy Xiao; Zhang Jb; XQ Gu; WL Lee; Kathryn M. Kauffman; WP Hanage; Marcelo Matus; Newsha Ghaeli; Noriko Endo; Claire Duvallet; Katya Moniz; et al. (2020)
Abstract Wastewater surveillance may represent a complementary approach to measure the presence and even prevalence of infectious diseases when the capacity for clinical testing is limited. Moreover, aggregate, population-wide data can help inform modeling efforts. We tested wastewater collected at a major urban treatment facility in Massachusetts and found the presence of SARS-CoV-2 at high titers in the period from March 18 - 25 using RT-qPCR. We then confirmed the identity of the PCR product by direct DNA sequencing. Viral titers observed were significantly higher than expected based on clinically confirmed cases in Massachusetts as of March 25. The reason for the discrepancy is not yet clear, and until further experiments are complete, these data do not necessarily indicate that clinical estimates are incorrect. Our approach is scalable and may be useful in modeling the SARS-CoV-2 pandemic and future outbreaks.